ANALISIS AKUNTABILITAS BELANJA BANTUAN SOSIAL PADA PEMERINTAH KOTA MANADO - Puasa, Flayer; Tinangon, Jantje J.; Manossoh, Hendrik (Universitas Sam Ratulangi, 2021)
This study aims to analyze the suitability of the accountability of social aid expenditures in the Manado City Government with applicable regulations, to analyze the obstacles faced in the implementation of social aid expenditure accountability and the efforts made by the Manado City Government to increase the accountability of social aid expenditures. This study uses a qualitative method with an exploratory case study approach. Data were obtained through in-depth interviews, documentation studies and observation.The results of the study indicate that the accountability of social aid expenditures in the Manado City Government has been implemented based on the regulations set by the government, although in its management there are still some obstacles. These constraints are human resource competence, compliance, sanctions, coordination, monitoring and regulation. Of the seven processes for managing social aid expenditures, the accountability and reporting processes are the processes that often experience problems, namely human resource competence, compliance, coordination and monitoring. Meanwhile, efforts that have been made to increase the accountability of social aid expenditures are by conducting socialization and requesting accountability reports to recipients of social assistance.Furthermore, there are several things that are recommended to increase the accountability of social aid expenditures to the Manado City Government, namely: it is necessary to pay attention to the balance of the use of human resources between the number of staff needed (quantity) and the expertise (competence) possessed; strict sanctions must be regulated in regulations and actually implemented; it is necessary to have an initiative from the manager in this case the related SKPD to study the regulations that become a reference on the main tasks and functions in the management of social aid expenditures; coordination between fellow social aid managers needs to be carried out; the manager is obliged to assist the recipient in preparing the accountability report; in addition to sending letters and making calls, requests for accountability reports need to be followed up by picking up directly from the recipient; managers need to provide an accountability report format, because in addition to assisting recipients in making accountability reports, they also facilitate auditors in conducting audits.